Media, Death, Dialogue. Social and Media Values in the Discourse about the ‘Family’ Suicides in Bulgaria - Petar Kanev (Communication Today, 2025)
How media confront abnormal social trends speaks volumes about the prevailing social and journalism norms and values. Bleak economic and social conditions may give rise to suicides, which classical sociological theory views as a strong indicator of a society in a serious crisis and in need of reconstruction. Media coverage and especially comments on such grave events demonstrate the capacity and willingness of journalists to engage in a sensible communication on the issue, or attempt to divert the public’s attention from the crux of the matter. A value analysis is thus revealing of media’s motivation and the eventual outcome of its thorough or selective highlighting of an alarming situation. The study employs a qualitative type of content analysis to discover the willingness of media to engage in an honest dialogue on the larger picture. The conclusion is hardly optimistic: media in Bulgaria tend to eschew dialogue, provide narrow technocratic explanations of tragedies, developing insensitive blind spots for the wider reality, the social and the human, thus failing its mission. Since values change slowly and under the influence of long-term factors, this study provides an insight on the way cultivation forces have worked in the Bulgarian society and media.